Research on Circulating Current Control Strategy for Parallel VSG Based on Adaptive Virtual Impedance (International Conference on Energy, Intelligence Systems, and Cloud Computing (Ingenio 2026), 2026)
To address the circulating current and uneven power distribution issues in multi-virtual synchronous generator (VSG) parallel systems caused by inconsistent line impedances, an improved control strategy introducing dynamic virtual impedance is proposed. By analyzing the active power-frequency and reactive power-voltage control characteristics of VSG, the influence mechanism of line impedance differences on power distribution accuracy and circulating current is revealed. In the proposed strategy, adaptive virtual impedance is introduced to enhance the inductive feature of the output impedance, achieving power decoupling, and a voltage feedback integral link is combined to compensate for the voltage drop caused by virtual impedance. Simulation results show that this strategy can effectively suppress the circulating current between parallel VSGs, achieve precise sharing of active and reactive power, and improve system stability and power quality.
Keywords: Virtual synchronous generator (VSG), Circulating current, Power sharing, Dynamic virtual impedance.